2014
DOI: 10.1186/1471-2180-14-39
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire of novel sequence signatures for the detection of Candidatus Liberibacter asiaticus by quantitative real-time PCR

Abstract: BackgroundHuanglongbing (HLB) or citrus greening is a devastating disease of citrus. The gram-negative bacterium Candidatus Liberibacter asiaticus (Las) belonging to the α-proteobacteria is responsible for HLB in North America as well as in Asia. Currently, there is no cure for this disease. Early detection and quarantine of Las-infected trees are important management strategies used to prevent HLB from invading HLB-free citrus producing regions. Quantitative real-time PCR (qRT-PCR) based molecular diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…L. solanacearum' ZC1 were also predicted to be specific to this genome and annotated by RAST as hypothetical proteins (again, most were less than 70 amino acid residues in length). The lack of clarity surrounding the predicted function of many of these haplotype-or species-specific orthologs is consistent with Kogenaru et al (2014), who identified 18 coding sequences in 'Ca. L. asiaticus' that were not present in 'Ca.…”
Section: (Continued On Next Page)supporting
confidence: 69%
See 1 more Smart Citation
“…L. solanacearum' ZC1 were also predicted to be specific to this genome and annotated by RAST as hypothetical proteins (again, most were less than 70 amino acid residues in length). The lack of clarity surrounding the predicted function of many of these haplotype-or species-specific orthologs is consistent with Kogenaru et al (2014), who identified 18 coding sequences in 'Ca. L. asiaticus' that were not present in 'Ca.…”
Section: (Continued On Next Page)supporting
confidence: 69%
“…Genome sequences have been used to develop tools for investigating genetic variability and improved detection of 'Ca. L. asiaticus' (Katoh et al 2011, Kogenaru et al 2014. Such tools are important for characterizing the strains used in biological experiments.…”
mentioning
confidence: 99%
“…It is proposed that two important strategies for prevention are sensitive detection methods and a healthy seedling system. In recent years, quantitative detection methods have been developed and improved for more sensitive and specific purposes (Li et al ., , ; Morgan et al ., ; Ananthakrishnan et al ., ; Hu et al ., ; Bertolini et al ., ; Kogenaru et al ., ; Feng et al ., ). Quantitative methods have been used to analyse the distribution of Las, showing uneven patterns in different infected tissues of various citrus cultivars (Tatineni et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy has also been used for the diagnosis of diseased citrus plants, and mid-infrared spectroscopy has been used to study citrus greening infection; however, except for the LIBS method, these studies did not provide early diagnosis. Early detection and quarantine of Las-infected trees are important management strategies used to prevent HLB from invading HLB-free citrus-producing regions (Kogenaru et al 2014). In this review, we describe the current diagnostic techniques for HLB disease performed worldwide, because an early diagnosis and differentiation of Ca.…”
Section: Introductionmentioning
confidence: 99%
“…HLB symptoms can be confused with diseases like Citrus Tristeza Closterovirus, Phytophthora infection, citrus blight, and certain nutrient deficiencies (Shokrollah et al 2011). Methods such as electron microscopy, serology, DNA probes, enzymatic assay, enzyme-linked immunosorbent assays (ELISA), conventional polymerase chain reaction (PCR) (Yamamoto et al 2006), and quantitative PCR (qPCR) are used for the diagnosis and confirmation of HLB (Kogenaru et al 2014). X-ray fluorescence and laser-induced breakdown spectroscopy (LIBS) combined with chemometric strategies are used to successfully predict the condition of orchard plants infected with Ca.…”
Section: Introductionmentioning
confidence: 99%